Development of perovskite-based light emitting diodes with improved stability 4.0 - Keng, Jia Qi (Nanyang Technological University, 2020)
It has been found that all-inorganic Cesium Lead Halide CsPbX3 (X= Cl, Br, I) perovskite quantum dots are potential luminescent candidates which are promising materials for optoelectronics and future energy applications. However, a major obstacle that perovskites faced is the overcoming of its poor stability. With degradation factors from the environment condition, it causes these perovskites to be affected. Hence, in this project, several experiments are carried out to improve the stability of the perovskite quantum dots. Microwave irradiation, hot-injection method and precipitation method are conducted to test for the luminescence and photoluminescence quantum yield of the purified nanocrystals obtained from the experiment. To improve the stability of perovskite quantum dots, type of ligand used in the synthesis method will be substituted by 3-Aminopropyltriethoxysilane. By measuring the photoluminescence quantum dots, it deduced that the substitution of ligand is able to improve the stability of the perovskite quantum dots.